Análise térmica aplicada ao estudo de materiais energéticos Thermal analysis applied to the study of energetic materials - Jony Andrade; Koshun Iha; Jose Atílio Fritz Fidel Rocco; Eduardo Marcelo Bezerra; Maria Encarnación Vázquez Suárez-Iha; Glaci Ferreira Martins Pinheiro (Química Nova, 2007)
This paper shows different aspects related to the application of different thermal analysis techniques in the study of energetic materials. The criteria used to choose the best technique and an exact approach to adjust the experimental data with a proper model are here discussed. The paper shows how to use the different thermal analysis results to help develop new compounds, to study the stability of some energetic materials and their compatibility, and the conditions necessary for a secure storing environment.